A Comprehensive Systematic Review of Nutritional Interventions For The Prevention of Maternal Morbidity - Fajar Nurochman Sidik; Dhimas Muhammad Suharyo (The International Journal of Medical Science and Health Research, 2024)
Background: The reviewed literature highlights the significant impact of nutritional interventions on preventing maternal morbidity and improving health outcomes for mothers and infants, particularly in low- and middle-income countries (LMICs). The systematic review by (Alemu Zerfu & Taddese Ayele, 2013) emphasizes the alarming prevalence of micronutrient deficiencies among pregnant women, particularly in regions like southern Asia and sub-Saharan Africa, where low birth weight and maternal undernutrition are critical issues. The authors advocate for multiple micronutrient supplementation as a vital strategy to enhance maternal health and reduce adverse pregnancy outcomes, while also calling for further research to address the variability in trial results. Literature Review: (Mousa et al., 2019) provide an overview of the increased nutritional demands during pregnancy, underscoring that dietary intake alone often cannot meet these needs. They advocate for supplementation and food fortification programs to address overlooked nutrients and improve maternal and fetal health. Similarly, (Oh et al., 2020) argue for prioritizing multiple micronutrient supplementation over traditional iron and folic acid alone, as it has shown significant benefits in reducing stillbirth and low birth weight, especially in LMICs. (S Lassi et al., 2020) further explore the effectiveness of antenatal macronutrient supplementation and food distribution programs, finding that balanced energy protein supplementation can significantly reduce perinatal mortality and improve birth weight. They emphasize the importance of addressing both micro- and macronutrient deficiencies to mitigate maternal and neonatal complications.  Conclusion: In conclusion, the synthesis of evidence from these studies illustrates the complexity of nutritional needs during pregnancy and the potential for targeted interventions to address these challenges. The urgent need for effective nutritional interventions, particularly in LMICs, is clear, as they play a crucial role in combating maternal morbidity and improving health outcomes for both mothers and infants.